An international perspective on the people and events shaping science education in Taiwan—past, present, and future - Yore, L.; Shymansky, J.; Treagust, David (Springer Singapore, 2016)
© Springer Science+Business Media Singapore 2016. This reflection considers the array of women, men, and events that have contributed to the research and development of science education in Taiwan during the last 50 years. The chapter explores the documents, programs, institutions, and scholars that have influenced science education in Taiwan at the local, national, and international levels. In this chapter, the authors begin their study by discussing the successes, challenges, and promises of science education in Taiwan via e-mail an d face-to-face meetings, to establish tentative trends and assertions based on their nearly 80 years of combined experience in Taiwan. They were among some of the early visiting science educators to Taiwan in the 1980–1990s and continue to consult and visit until the present time. They have served as founding senior and associate editors of the International Journal of Science and Mathematics Education, a research journal with roots in Taiwan. More than 50 years were partitioned into more manageable periods: pre-1980, 1980–2010, and post-2010. The authors then proceed to collect information from websites, science educators, and journals to verify and elaborate these trends and assertions. They informally interview inter National science educators who were involved in Taiwanese projects to map out some of the potential critical events and people. Next, they survey past (retired), present (active and established), and future (postdoctoral fellows and recently appointed faculty members) science educators in Taiwan using a simple e-mail questionnaire. Completed surveys are analyzed, seeking evidence to support or modify these trends and assertions. As a final step, the authors consider the content of research articles published in English-language journals to determine the research foci and trends during each period. They develop speculations about what occurred and what had been promised.